Prevalence of Marriage Abstinence and its Associated Factors among Saudi Youth: A Cross-Sectional Study - Albrahim, Aljawhara; Azman, Azlinda (Advances in Social Sciences Research Journal, 2025)
The prevalence of marriage abstinence, which is related to social and economic factors, has recently raised social concerns in Saudi Arabia. This study aimed to identify the social and economic factors leading to marriage abstinence among young people in Saudi Arabia. A cross-sectional study was conducted with 575 participants selected using a simple convenience sampling technique. Data were collected using a self-administered online questionnaire. The results of the study revealed that the prevalence of marriage abstinence among young Saudis was 46.8%. The social factors (personal factors, attitude factors, family factors and women empowerment) constituted 57.6%, while economic factors (living costs, marriage costs and job and salary) constituted 62.2% of marriage abstinence reasons. There was a significant association between age, gender, education level, job, employment and monthly income (p<0.05) with the marriage abstinence. Furthermore, social and economic factors were statistically positively correlated with agreeableness, openness, and neuroticism and negatively correlated with conscientiousness. The high prevalence of marriage abstinence in Saudi Arabia is of great concern. Education and community awareness programs are needed to mitigate the problem of marriage abstinence. Furthermore, setting dowries, providing jobs, solving the housing problem, and providing soft loans can contribute to reducing the problem of marriage abstinence.